Avaliação nutricional de pacientes com insuficiência renal crônica com ou sem diurese residual submetidos à hemodiálise - Fidale, Beatriz Montes (2011)
Objective: The objective of this study was to compare the parameters of nutritional evaluation in the presence or absence of residual diuresis in chronic kidney patients submitted to hemodialysis (HD). Methods: This transversal study evaluated 43 chronic kidney patients undergoing HD; their average age was 53.5 ± 11.6 years and the average time of diuretic treatment 22.1± 13.9 months. To acess the nutritional status, were measured weight, eight, tríceps skinfold thickness (TSF), biceps, subescapular and suprailiac, beyong the midarm circunference (MAC). In order to evaluate their nutritional state, body mass index (BMI), body fat (BF) and the muscular circumference of the arm were evaluated. The Subjective Global Assessment (SGA) was used for diagnosis of the nutritional state. Albumin, creatinine and total cholesterol (CT) were collected. Through the normalized protein equivalent of total nitrogen appearance (nPNA) and of a 3 day food register, protein-energy intake was estimated. The adequacy of dialysis was evaluated by Kt/V and a 24 hour urine collection was performed. According to the measure of urine volume, the individuals were divided in: group D- (0 400 ml) and group D+ (>400ml). Results: In anthropometry, group D- presented average values inferior to those of group D+ in the calculations of BMI (22.4 ± 3.5 kg/m2 vs 24.9 ± 3.8 kg/m2, p=0.034) and of BF (24.2 ± 8.0 % vs 31.3 ± 8.4 %, p=0.007), in the measure of SKF (12.6 ± 5.4 mm vs 17.0 ± 6.9 mm, p=0.022) and in the adequacy of MAC (93.5 ± 11.8 % vs 102.6 ± 12.34 % , p=0.021). In accordance with TSF adequacy, group D- was classified as undernourished (<90%) and group D+ as eutrophic (90-110%). According to the SGA diagnosis, both group D- and D+ presented a prevalence of elevated nutritional risk (84% and 88.9% respectively) and D- had a prevalence of moderate/severe undernourishment three times greater than D+ (16% vs 5.5%). The average protein energy intake was similar in both groups. Only group D- presented a low value of CT (148.8 ± 55.2 mg/dl), which is considered nutritional risk. Albumin did not act as a marker of malnutrition with an average superior to the value recommended for this population both in D- (3.8 ± 0.35 g/dl) and in D+ (3.8 ± 0.55 g/dl. p=0.903). Conclusion: Patients with smaller urinary volume presented a reserve of body fat and lean body mass inferior to the patients with normal diuresis, thus manifesting the importance of the preservation of the volume of residual diuresis in dialytic treatment.